1974
DOI: 10.1111/j.2044-8279.1974.tb00780.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pendulum Problem: Patterns of Performance Defining Developmental Stages

Abstract: Summary. Performance on Inhelder and Piaget's pendulum problem was obtained as a validating measure in a study of the transition from concrete to formal thinking. The sample consisted of 236 children aged from 10 to 14 years. A detailed scoring procedure was devised, which distinguished method from content aspects of performance on the problem and which allows categorisation of each child into one of nine developmental stages. Quantitative performance scores were also derived. Overall level of performance on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 4 publications
2
8
0
1
Order By: Relevance
“…This is in full agreement with the observations of Sommerville (1974) and Shayer et al (1976). Also each student's success depends on the task set.…”
Section: Discussionsupporting
confidence: 86%
“…This is in full agreement with the observations of Sommerville (1974) and Shayer et al (1976). Also each student's success depends on the task set.…”
Section: Discussionsupporting
confidence: 86%
“…As the original Genevan method, the méthode clinique remains the conventional means of investigating operational ability (Dale 1970;Lovell 1961;Somerville 1974). However, during the course of testing in the present study, three procedural aspects in the administration of the pendulum problem were identified which provide potential for misinterpretation of performances in the individual méthode clinique situation.…”
Section: Evaluation Of Méthode Cliniquementioning
confidence: 85%
“…While replications of Piaget's work (Lovell 1961;Pauli et al 1974;Somerville 1974) have shown the accuracy of the méthode clinique in eliciting cognitive competence and differentiating between operational levels, they also describe its limitations in that the method is time-consuming and requires considerable expertise for administration and interpretation. Researchers interested in empirical studies have also argued "that results obtained by such a flexible procedure as the méthode clinique do not lend themselves to statistical treatment" (Wallace 1965, p. 58).…”
Section: Measuring Formal Operationsmentioning
confidence: 95%
See 2 more Smart Citations